Experimental tests on shear capacity of naturally corroded prestressed beams. (24th August 2020) - Belletti, Beatrice; Rodríguez, Jesús; Andrade, Carmen; Franceschini, Lorenzo; Sánchez Montero, Javier; Vecchi, Francesca
Abstract: An experimental campaign was carried out on full‐scale naturally corroded prestressed concrete (PC) beams without transverse reinforcement to investigate the corrosion effects on failure modes, shear capacity, and ductility. The analyzed PC beams, structural members of a thermal power plant, were subjected for 10 years to refrigerating wetting cycles with marine water. In this paper, the experimental results of four‐point bending tests, carried out at the Institute "Eduardo Torroja" in Madrid, are described. Before tests, a visual inspection was conducted to detect the damages induced by corrosion. During the tests, displacements and strains were measured by using linear variable displacement transducer (LVDT) and digital image correlation (DIC). After the tests, strands were removed from beams and cut in pieces, which were weighed to measure the mass loss. Last, it was proved that the residual life of PC beams, exposed to chloride attack, is strongly affected by corrosion, whose effects reduce the shear capacity in terms of both resistance and ductility.